Link and Match Socialization of Maritime Vocational College Graduates in the Field of Shipping with the Business and the Industrial World - Astriawati, Ningrum; Dekanawati, Vivid; Sahudiyono, Sahudiyono; Kusuma, Ade Chandra; Subekti, Joko; Handojo, Budi (PT Inovasi Pratama Internasional, 2024)
The